Localized activity attenuates the combined impact of a high fat meal and prolonged sitting on arterial stiffness: A randomized, controlled cross-over trial - Fryer, Simon; Paterson, Craig; Turner, Louise; Moinuddin, Arsalan; Faulkner, James; Stoner, Lee; Daykin, Anne; Stone, Keeron (Frontiers in Physiology, 2023)
Exposure to acute prolonged sitting and consumption of a high fat (HF) meal have been shown to independently and additively impair central and peripheral cardiovascular function. This study sought to determine whether localised activity, namely leg fidgeting, offers a protective effect to these deleterious effects. Using a randomized crossover design with three trials, 18 healthy males sat uninterrupted for 180 min following the consumption of a low fat (LF, trial 1) or HF meal (trial 2). The third trial consisted of a HF meal but sitting was interrupted with 1 min of leg fidgeting (isolated bilateral plantar flexion) consisting of ~250 taps per min every 5 min for the 180 min duration. Carotid-femoral pulse wave velocity (cfPWV), aortic-femoral stiffness gradient (af-SG), superficial femoral blood flow, shear-rate and PWVβ, triglyceride concentrations and lower-limb venous pooling (HHb) were assessed pre and post sitting in all trials. General linear mixed model found that following the uninterrupted HF trial, there was a significant worsening of cfPWV (mean difference (MD)= 0.57 mˑs-1; d= 1.04) and the af-SG (MD= 0.14, d= 0.50), and femoral artery blood flow (MD= 18 mlˑmin-1; d= 0.48) and shear rate (MD= 15 S1; d= 0.67) decreased. However, leg fidgeting was enough to prevent the combined deleterious effects of prolonged sitting following a HF meal. As there were no significant changes in the LF trial, the HF meal maybe the predominant driver when uninterrupted sitting is combined with a HF meal.